2010
DOI: 10.2215/cjn.01230210
|View full text |Cite
|
Sign up to set email alerts
|

Does the Heparin Lock Concentration Affect Hemodialysis Catheter Patency?

Abstract: Background and objectives: Concentrated heparin solutions are instilled into the catheter lumens after each hemodialysis session to prevent catheter thrombosis. The heparin lock concentration at many centers has been decreased recently to reduce the risk of systemic bleeding and contain costs. However, the effect of this change on catheter patency is unknown. We compared catheter patency between two heparin lock solutions: 1000 versus 5000 units/ml. Design, setting, participants, & measurements: With use of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
18
1
2
Order By: Relevance
“…10 In clinical practice, anticoagulant (e.g., heparin, citrate) and antibiotic lock solutions are also used. 1, 1112 Lock solutions containing anticoagulants are employed to prevent local thrombus formation, but have had similar rates of thrombosis and fail to address issues related to microbial infection. 11, 13 Catheter replacement is the only solution in many cases, which can further increase chances of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In clinical practice, anticoagulant (e.g., heparin, citrate) and antibiotic lock solutions are also used. 1, 1112 Lock solutions containing anticoagulants are employed to prevent local thrombus formation, but have had similar rates of thrombosis and fail to address issues related to microbial infection. 11, 13 Catheter replacement is the only solution in many cases, which can further increase chances of infection.…”
Section: Introductionmentioning
confidence: 99%
“…1, 1112 Lock solutions containing anticoagulants are employed to prevent local thrombus formation, but have had similar rates of thrombosis and fail to address issues related to microbial infection. 11, 13 Catheter replacement is the only solution in many cases, which can further increase chances of infection. 1415 Development of polymers that can resist both thrombosis and infection is still a prominent area of research with the potential for significant clinical benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In various other protocols, investigators compared the effectiveness of different heparin concentrations (5000 or 10,000 units/ml versus 1000 units/ml) in maintaining catheter patency. Although the incidence of catheter malfunction did not change with the lower dose of heparin as a prophylactic locking solution, the use of tPA to maintain patency increased significantly (25)(26)(27).…”
Section: Changes In Blood Flow: the Use Of Catheter-locking Solutionsmentioning
confidence: 93%
“…Thomson et al 21 report that using 1000 UI/mL heparin involves reduced risk of systemic heparinization than the usual 5000 UI/ mL dosage, without increasing rates of infection, catheter loss or malfunction. However, Ivan et al 22 used the same concentrations of heparin and showed that although catheter patencies were similar in both groups, the group given 1000 UI/mL needed twice the volume of thrombolytics infused to deobstruct catheters. At our department, routine procedure is to fill catheters with heparin 5000 UI/mL.…”
Section: Central Venous Cathetersmentioning
confidence: 99%